EVALUATION OF UPPER AIRWAY DIMENSION IN ALL FOUR FIRST PREMOLAR EXTRACTION CASES - Pervez, Hana; Naseer, Anita; shah, Sara; Haqqui, Rabia; Naseer, Anita; Azam, Faiza; Ahmed, Warisha (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To find out any noticeable size difference in the superior airway at the end of premolar extraction treatment and to find out the effects of extraction on axial inclinations of anterior teeth. Methodology: It was a retrospective quasi-experimental study that consisted of 30 orthodontic patients in which all four first premolars were extracted. The orthodontic treatment of the participants was done at Department of Orthodontics, Jinnah Medical and Dental College, Karachi. The data was collected from January 2020 to March 2020. Sampling technique selected was consecutive which is a non- probability type of sampling. The cases included in this study were skeletal and dental class I having class I molar relationship with crowding that required all four first premolar extractions. Patients having syndromes or in need of orthognathic surgery were excluded from this study. The analysis was done on Lateral Cephalometric radiograph which was captured in the beginning and another one once treatment was completed. On these radiographs, changes in the soft palate and upper airway widths were measured. Results: No appreciable alterations observed in the superior airway and soft palate widths. The difference observed in the upper incisors inclination was significant when compared to their pretreatment values. Conclusion: No appreciable change has been noted in the airway dimensions after extraction of premolars. The extractions done as a part of orthodontic treatment results in a great improvement in the correction of proclinations of anterior teeth and reduction of lip procumbency. Key Words: Premolar extractions, Lateral Cephalogram, Airway